Gender Inequality and Its Psychological Impacts - Abdullaeva Mokhidil Esanbaevna (Euro Asian Journal Publishing, 2024)
The article explains what gender inequality is, and how it impacts society. Also, it discusses potential causes of gender inequality and its psychological impacts on the people who are suffering from gender inequality
Keywords: gender inequality issues; causes of gender inequality